2022
DOI: 10.48550/arxiv.2205.08306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accurate Machine Learned Quantum-Mechanical Force Fields for Biomolecular Simulations

Abstract: Molecular dynamics (MD) simulations allow atomistic insights into chemical and biological processes. Accurate MD simulations require computationally demanding quantum-mechanical calculations, being practically limited to short timescales and few atoms. For larger systems, efficient, but much less reliable empirical force fields are used. Recently, machine learned force fields (MLFFs) emerged as an alternative means to execute MD simulations, offering similar accuracy as ab initio methods at orders-of-magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Due to the limitations of classical FFs, however, there is strong interest in increasing the accuracy of biomolecular simulations. Deep learning interatomic potentials have been applied to biomolecular systems in hopes of achieving higher accuracy [29], but only 25k atom scale has been reached due to the lack of scalability of MPNNs [30]. In parallel, hybrid approaches have been explored that only treat the solute-solute interactions with the MLIP, while solventsolvent and solvent-solute interactions were modelled with a classical polarizable force-field [31].…”
Section: Yesmentioning
confidence: 99%
“…Due to the limitations of classical FFs, however, there is strong interest in increasing the accuracy of biomolecular simulations. Deep learning interatomic potentials have been applied to biomolecular systems in hopes of achieving higher accuracy [29], but only 25k atom scale has been reached due to the lack of scalability of MPNNs [30]. In parallel, hybrid approaches have been explored that only treat the solute-solute interactions with the MLIP, while solventsolvent and solvent-solute interactions were modelled with a classical polarizable force-field [31].…”
Section: Yesmentioning
confidence: 99%
“…In the past, several methodologies were developed to achieve reactive MD, including reactive force elds, such as ReaxFF 41 and AIREBO, 42 hybrid quantum mechanical/molecular mechanical (QM/MM) 43 simulations, and, more recently, molecular dynamics simulations paired with machine-learned force elds (MLFF). 44,45 However, all these methods are slower compared to regular MD 46 and are by default restricted to reactions on the timescale of the simulation. KIMMDY overcomes these drawbacks but relies on the availability of reaction rates, which can now be provided with the model introduced here.…”
Section: Discussionmentioning
confidence: 99%
“…This causes a truncation of long-range interactions, which, in local models, are assumed to have a rather small contribution to the overall dynamics of the system. Nonetheless, it has been shown that long-range effects can play an important role (8)(9)(10)(11)(12), limiting the predictive power of local models in nanoscale and mesoscale systems (13,14). Several recent MLFF models (8,9,(15)(16)(17)(18)(19)(20) introduce empirical correction terms for specific long-range effects (e.g., electrostatics), yet longrange electron correlation effects remain poorly characterized.…”
Section: Introductionmentioning
confidence: 99%